On Perceived Stress and Social Support: Depressive, Anxiety and Trauma-Related Symptoms in Arabic-Speaking Refugees in Jordan and Germany - Böge, Kerem; Karnouk, Carine; Hahn, Eric; Demir, Zaynab; Bajbouj, Malek (Frontiers in Public Health, 2020)
Current literature points towards several challenges in the access to sufficient and effective psychosocial care for Syrian refugees in host settings. This study is a comparative investigation into the relationship between ‘perceived social stress’ and ‘perceived social support’ on three of the most prevalent symptom dimensions in Syrian refugees across two host capitals, Berlin and Amman. 89 Syrians refugees were recruited between January 2017 and March 2018. Participants were contacted through local institutions and organisations collaborating with the Charité – Universitätsmedizin Berlin. Assessments include the PHQ-9, GAD-7, HTQ, MSPSS and PSS. Primary analyses consist of non- or parametric tests and multiple linear regression analyses. Subsample analyses showed relevant depressive, anxiety and trauma-related symptoms. Significant differences in PTSD symptoms (p < 0.04) were found. Participants reported high perceived stress and moderate to high social support. Linear regressions revealed that perceived stress had a significant negative effect (p < 0.01) on clinical outcomes in both subsamples. Perceived social support had a positive influence on depressive (p = 0.02) and PTSD symptoms (p = 0.04) for participants in Berlin. Analyses revealed significant positive effects of ‘significant others’ (p = 0.05) on depressive- in Berlin and ‘family’ (p = 0.03) support for PTSD symptoms in Amman. Study results show that levels of ‘perceived stress’ appear to be the same across different host countries, whereas types of social support and their effect on mental health differ significantly depending on the host setting. Outcomes may guide future comparative study designs and investigations to promote well-being, integration and the development of effective social support structures for the diverse needs of Arabic-speaking refugees.